2014
DOI: 10.1016/j.bbamem.2014.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Cationic liposomes formulated with DMPC and a gemini surfactant traverse the cell membrane without causing a significant bio-damage

Abstract: Cationic liposomes have been intensively studied both in basic and applied research because of their promising potential as non-viral molecular vehicles. This work was aimed to gain more information on the interactions between the plasmamembrane and liposomes formed by a natural phospholipid and a cationic surfactant of the gemini family. The present work was conducted with the synergistic use of diverse experimental approaches: electro-rotation measurements, atomic force microscopy, ζ-potential measurements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 71 publications
3
26
0
Order By: Relevance
“…A previous study has indicated that the HANPs, only within the cell nucleus, could induce cytotoxicity, while the HANPs that remained in the perinuclear region or cytoplasm only caused local modifications to the morphology and structure of the cell membrane and exerted negligible inhibitory effects. 35,36,37 However, our results suggested that HANPs might interact with organelles, such as chondriosome and lysosomes (Figure 3), thus interfering with HUVEC survival and function although they concentrated in the cytoplasm (Figures 2 and 7). The uptake of NPs originated from an event of NPs adhering to the cell membrane, and this process was followed by the actual internalization via energy-dependent uptake pathways.…”
Section: Discussionmentioning
confidence: 57%
“…A previous study has indicated that the HANPs, only within the cell nucleus, could induce cytotoxicity, while the HANPs that remained in the perinuclear region or cytoplasm only caused local modifications to the morphology and structure of the cell membrane and exerted negligible inhibitory effects. 35,36,37 However, our results suggested that HANPs might interact with organelles, such as chondriosome and lysosomes (Figure 3), thus interfering with HUVEC survival and function although they concentrated in the cytoplasm (Figures 2 and 7). The uptake of NPs originated from an event of NPs adhering to the cell membrane, and this process was followed by the actual internalization via energy-dependent uptake pathways.…”
Section: Discussionmentioning
confidence: 57%
“…A smaller value of their cmc also enables them to be efficient solubilisers of low soluble drugs [19], dyes [20,21], hydrocarbons such as n-hexane and toluene [22]. Gemini surfactants can also serve as structural units in the formulation of cationic liposomes [23]. As for industrial applications, gemini surfactants show inhibitive effect on iron corrosion [24], act as efficient agents in oil recovery [25], styrene polymerisation [26,27], dying of textiles [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22][23][24] Among the existing nonviral vectors, the cationic liposome, representing an attractive, alternative approach for gene delivery has a broad varity of advantages, such as biodegradability, easy preparation, good repeatability and potential clinical applications. [25][26][27][28][29] Cationic lipids generally consist of polar head group and hydrophobic tails connected through the backbone (Fig.…”
mentioning
confidence: 99%